Comparability of retinal nerve fiber layer thickness measurements of optical coherence tomography instruments - Bourne, Rupert R A; Medeiros, Felipe A; Bowd, Christopher; Jahanbakhsh, Keyvan; Zangwill, Linda M; Weinreb, Robert N (Investigative ophthalmology & visual science, 2005)
To compare retinal nerve fiber layer (RNFL) measurements between two ocular coherence tomography (OCT) instruments (OCT 2000 and Stratus OCT; Carl Zeiss Meditec, Dublin, CA) and compare their diagnostic precision. One hundred thirty-nine consecutive subjects were imaged (3 x 3.4-mm diameter circular scans) on the same day with each instrument. Thirty-five patients were excluded due to poor-quality images. RNFL thicknesses measured by the two instruments were compared, and receiver operating characteristic (ROC) curves were used to determine diagnostic precision. A randomly selected eye of each of 104 participants (28 with open-angle glaucoma, 40 with suspected glaucoma, and 36 healthy subjects) was analyzed. RNFL thickness measurements generally were thicker with OCT 2000 than with Stratus OCT. The difference in global RNFL thickness between instruments was within 20 microm in 66 (65%) of subjects and within 10 microm (the instrument's limit of resolution) in 25 (25%) subjects. Application of a correction factor to OCT 2000 measurements predicted Stratus OCT RNFL thickness within 10 microm of the observed measurement in 75% of the eyes. For both instruments, highest ROC curve areas (better discrimination between glaucomatous and normal eyes) were found in the inferior sector. Discrimination using global RNFL thickness was better with Stratus OCT than OCT 2000 (P = 0.043). RNFL thickness measurements measured by OCT 2000 can be approximated to measurements made by Stratus OCT using correction factors calculated by this study. However, there remains considerable variability that exceeds the limits of resolution afforded by the instruments themselves. Therefore comparisons between instruments using these approximations should be interpreted with caution.